Epidemiology and One-Year Follow-Up of Neonates with CDH-Data from Health Insurance Claims in Germany - Boris Wittekindt; Nora Doberschuetz; Andrea Schmedding; Till-Martin Theilen; Rolf Schloesser; Stefan Gfroerer; Udo Rolle (MDPI AG, 2021)
Congenital diaphragmatic hernia (CDH) is a major congenital malformation with high mortality. Outcome data on larger unselected patient groups in Germany are unavailable as there is no registry for CDH. Therefore, routine data from the largest German health insurance fund were analyzed for the years 2009-2013. Main outcome measures were incidence, survival and length of hospital stay. Follow-up was 12 months. 285 patients were included. The incidence of CDH was 2.73 per 10,000 live births. Overall mortality was 30.2%. A total of 72.1% of the fatalities occurred before surgery. Highest mortality (64%) was noted in patients who were admitted to specialized care later as the first day of life. Patients receiving surgical repair had a better prognosis (mortality: 10.8%). A total of 67 patients (23.5%) were treated with ECMO with a mortality of 41.8%. The median cumulative hospital stay among one-year survivors was 40 days and differed between ECMO- and non-ECMO-treated patients (91 vs. 32.5 days, p < 0.001). This is the largest German cohort study of CDH patients with a one-year follow-up. The ECMO subgroup showed a higher mortality. Another important finding is that delayed treatment in specialized care increases mortality. Prospective clinical registries are needed to elucidate the treatment outcomes in detail.